Psychology of Reading & Overcoming Reading Difficulties: An Overview - GEYLANİ, Özlem (PEARSON JOURNAL, 2023)
One of the most critical transversal abilities for success in both school and society is reading comprehension. Children who struggle with specific reading comprehension issues can effectively decode texts, but they have serious comprehension issues. Reading comprehension issues are common among elementary and secondary school pupils and can have detrimental effects on their academic performance. Fluency is one of the most important aspects of reading success. Phonology, orthography, and semantics are all necessary for reading, which is a higher-order cognitive skill that also depends on more fundamental cognitive skills like working memory, speed measurements, attention switching and shifting, and cognitive control (inhibition and concentration). The development of cognitive control and general growth of the brain are most important during childhood and adolescence. As a result, cognitive training given in childhood and adolescence might be more beneficial than cognitive training given in old age.